Comprehensive microsurgical anatomy of the middle cranial fossa: Part I—Osseous and meningeal anatomy - Tayebi Meybodi, Ali; Mignucci-Jiménez, Giancarlo; Lawton, Michael T.; Liu, James K.; Preul, Mark C.; Sun, Hai (Frontiers in Surgery, 2023)
The middle cranial fossa is one of the most complex regions in neurosurgery and otolaryngology—in fact, the practice of skull base surgery originated from the need to treat pathologies in this region. Additionally, great neurosurgeons of our present and past are remembered for their unique methods of treating diseases in the middle fossa. The following article reviews the surgical anatomy of the middle fossa. The review is divided into the anatomy of the bones, dura, vasculature, and nerves—in two parts. Emphasis is paid to their neurosurgical significance and applications in skull base surgery. Part I focuses on the bony and dural anatomy.